Gastrodiplomacy Indonesia di Belanda Era Pemerintahan Joko Widodo - Yeremias, Yeremias; Kurniawati, Erna (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
The purpose of this research is to identify kind of Indonesian diplomacy through gastrodiplomacy.